HUBUNGAN KEMANDIRIAN BELAJAR DAN MOTIVASI BELAJAR DENGAN HASIL BELAJAR BIOLOGI SISWA KELAS XI LINTAS MINAT DI SMA HANG TUAH TARAKAN - Ratna Ratna; Zulfadli Zulfadli; Vlorensius Vlorensius; Fatmawati Fatmawati (Program Studi Pendidikan Biologi Universitas Borneo Tarakan, 2022)
Abstract This research aimed to analyze the relationship of learning independence and laerning motivation with laerning achievement of Grade XI cross-major biology students at SMA Hang Tuah Tarakan. The study was correlation research using a descriptive correlational method with quantitative approach. The research population was 58 students with the samples collected using a total sampling technique. All data were obtained based on the questionnaire score on learning independence, learning motivation, and learning achievement from biology mid-semester test, and the analyzed using Multiple Linear Test of figure out the relationship of learning independence and learning motivation (X) with biology learning achievement (Y). The research result show that there is a relationship of learning independence and learning motivation with biology laerning achievement with the significance value of 0.0009 0.005. There was a relationship between learning independence and biology learning achievement with the significance value of 0.0042; and there was a relationship between learning motivation and biology achievement with the significance value of 0.020 0.005.Keywords: Independence, Motivation, Biology learning achievement